2008
DOI: 10.1136/sti.2008.031781
|View full text |Cite
|
Sign up to set email alerts
|

Increases in gonorrhea among high school students following hurricane Katrina

Abstract: The analysis indicates that the odds of testing positive for gonorrhea more than doubled among students after the hurricane, indicating that surveillance activities should be restored to monitor sexually transmitted infections (STIs) among at-risk populations. Redoubled efforts should be put into STI screening programmes as soon as possible following natural disasters to prevent resurgent STI incidence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…The New Orleans screening was offered to all students in participating schools regardless of sexual activity, symptoms of STIs or a history of STI. 7 This study adds that screening for STIs in schools should be offered regardless of students' perception of their risk of STI. The consistency in adolescents' perception of not being at high risk of STI across continents 9 -13 constitutes a strong indicator that overall, most participants in school-based screenings for chlamydia and gonorrhoea 1 -3,5,6,16 are likely to be individuals who do not perceive themselves at high risk of STI.…”
Section: Discussionmentioning
confidence: 97%
“…The New Orleans screening was offered to all students in participating schools regardless of sexual activity, symptoms of STIs or a history of STI. 7 This study adds that screening for STIs in schools should be offered regardless of students' perception of their risk of STI. The consistency in adolescents' perception of not being at high risk of STI across continents 9 -13 constitutes a strong indicator that overall, most participants in school-based screenings for chlamydia and gonorrhoea 1 -3,5,6,16 are likely to be individuals who do not perceive themselves at high risk of STI.…”
Section: Discussionmentioning
confidence: 97%
“…In one recent study, gonorrhea rates among high school students in New Orleans were compared pre- and post hurricane Katrina testing the hypothesis that deterioration in neighborhoods due to Katrina would result in higher gonorrhea rates. Results showed that testing positive for gonorrhea more than doubled after the hurricane (Nsuami et al 2009). Other studies have linked perceived neighborhood disorder to sexual risk behaviors associated with HIV and other STIs (Latkin et al 2007; Rhodes et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…25,27,38,44 In 2 programs, every grade 9 to 12 student was scheduled to attend an education/screening session 25 or students viewed a brief presentation in classrooms. In these 4 programs, students were approached in the classrooms for screening.…”
Section: Findings By Program Typementioning
confidence: 99%
“…25,27,38,44 In 2 programs, every grade 9 to 12 student was scheduled to attend an education/screening session 25 or students viewed a brief presentation in classrooms. 44 In the fourth program, female students were provided with screening information and test kits during lectures or lecture breaks, and specimens were returned on the next day. 25,27 The entire class was escorted to the testing area, and students were individually counseled for an opportunity to screen in the third program.…”
Section: Findings By Program Typementioning
confidence: 99%
See 1 more Smart Citation